TANGGUNG JAWAB HUKUM PERSEROAN TERBATAS (PT) YANG DINYATAKAN PAILIT - Purbandari, - (E-Journal Widya Yustisia, 2017)
Abstract: With the bankruptcy of an alleged Limited Liability Company, then treaseres will be in public and confiscated and the company will lose the treasure of his wealth. This will affect the existence of the company, where its administrator must be requested personally responsible written as the principle of Piercing The Corporate Veil. The purpose of this study is to (1) discuss the bankruptcy of a company, (2) the legal consequences of stated bankrupt company. The research methods using the juridical normative, which analysed qualitatively with data sourced from primary and secondary legal materials, and use the approach of law (statute approach) conducted by reviewing some of the legislation and other regulations relevant to the bankruptcy of a company. It can be concluded that: (1) the nature of bankruptcy is general encumbrances over the assets of the debtor are divided on the principle of balance; (2) due to the bankruptcy of a company is that company does not lose its existence, but the management dan liquidation process is done by the curator.